95.8k views
4 votes
(01.02) Given that f(x) = x2 + 3x + 6 and g(x) = the quantity of x minus three, over two , solve for f(g(x)) when x = 1. (1 point) −1 0 3 4

User Trax
by
5.5k points

2 Answers

2 votes

Answer:

4

Explanation:

took the test

User Jeyamaran
by
5.0k points
2 votes
In this composite you are going to stick the g function into the f function everywhere you see an x. So that will look like this:
f(g(x))=( (x-3)/(2) ) ^(2) +3( (x-3)/(2))+6. Putting in our x value of 1, now we have
f(g(1))=( (1-3)/(2)) ^(2) +3( (1-3)/(2) )+6. Simplifying that we have
f(g(1))=( (-2)/(2)) ^(2) +3( (-2)/(2)) +6 which of course simplifies to 1 - 3 + 6 which is 4
User Fadeproof
by
5.3k points